Factors Predicting Female Entrepreneurship Among University Students in the Lambayeque Region, Peru - Arbulú Ballesteros, Marco Agustín; Chuquitucto Cotrina, Lisseth Katherine; Paredes Morales, Ana Elizabeth; Arbulú Castillo, Julie Catherine; Martel Acosta, Rafael; Flores Lezama, Marilú Trinidad; Blas Sanchez, Julio Ernesto (LACCEI, 2024)
This study investigates entrepreneurial intention among female university students in Lambayeque, focusing on how various factors influence their inclination and ability to start businesses. A quantitative approach was adopted with a survey of 280 participants, analyzing factors such as the university environment, family background, socio-cultural context, personal attitude, and perceived internal control. The results indicate that the university environment and perceived internal control are significant predictors of entrepreneurial intention. Contrary to expectations, family support did not show a significant impact. A negative relationship was observed between the socio-cultural context and entrepreneurial intention, suggesting that certain cultural aspects may act as barriers. The conclusions highlight the importance of the academic environment and self-efficacy in fostering female entrepreneurship. The study challenges common perceptions about the role of family support and underscores the need to address socio-cultural barriers. Recommendations include strengthening entrepreneurial education in universities, enhancing students' self-efficacy, changing socio-cultural norms, and considering family involvement in the entrepreneurial process.